Β3‐Adrenoceptor stimulation of perivascular adipocytes leads to increased fat cell‐derived NO and vascular relaxation in small arteries. (10th August 2018) - Bussey, Charlotte E; Withers, Sarah B; Saxton, Sophie N; Bodagh, Neil; Aldous, Robert G; Heagerty, Anthony M
Abstract : Background and Purpose: In response to noradrenaline, healthy perivascular adipose tissue (PVAT) exerts an anticontractile effect on adjacent small arterial tissue. Organ bath solution transfer experiments have demonstrated the release of PVAT‐derived relaxing factors that mediate this function. The present studies were designed to investigate the mechanism responsible for the noradrenaline‐induced PVAT anticontractile effect. Experimental Approach: In vitro rat small arterial contractile function was assessed using wire myography in the presence and absence of PVAT and the effects of sympathomimetic stimulation on the PVAT environment explored using Western blotting and assays of organ bath buffer. Key Results: PVAT elicited an anticontractile effect in response to noradrenaline but not phenylephrine stimulation. In arteries surrounded by intact PVAT, the β3 ‐adrenoceptor agonist, CL‐316243, reduced the vasoconstrictor effect of phenylephrine but not noradrenaline. Kv 7 channel inhibition using XE 991 reversed the noradrenaline‐induced anticontractile effect in exogenously applied PVAT studies. Adrenergic stimulation of PVAT with noradrenaline and CL‐316243, but not phenylephrine, was associated with increased adipocyte‐derived NO production, and the contractile response to noradrenaline was augmented following incubation of exogenous PVAT with L‐NMMA. PVAT from eNOS −/− mice had no anticontractile effect. Assays of adipocyte cAMP demonstrated an increase with noradrenaline stimulation implicating Gαs signalling in this process. Conclusions and Implications: We have shown that adipocyte‐located β3 ‐adrenoceptor stimulation leads to activation of Gαs signalling pathways with increased cAMP and the release of adipocyte‐derived NO. This process is dependent upon Kv 7 channel function. We conclude that adipocyte‐derived NO plays a central role in anticontractile activity when rodent PVAT is stimulated by noradrenaline.